Chromosomal copy number analysis of products of conception by conventional karyotyping and next‐generation sequencing. (8th October 2020) - Tamura, Yuki; Santo, Mitsuo; Araki, Yasuhisa; Matsubayashi, Hidehiko; Takaya, Yukiko; Kitaya, Kotaro; Doshida, Masakazu; Yamaguchi, Kohei; Mizuta, Shimpei; Takahashi, Chie; Kim, Namhyo; Okuno, Koichiro; et al.
Abstract: Purpose: Chromosomal abnormalities are a major cause of spontaneous abortion, and conventional G‐banded karyotyping (G‐banding) is mainly utilized for chromosomal analysis. Recently, next‐generation sequencing (NGS) has been introduced for chromosomal analysis. Here, we aimed to investigate the applicability and utility of NGS‐based chromosomal analysis of products of conception (POC) on chorionic villus samples from spontaneous abortion. Methods: The results of chromosomal analysis of 7 chorionic villus samples from spontaneous abortion were compared between conventional G‐banding and NGS‐based chromosomal copy number analysis. Age dependency and frequency of each chromosomal aneuploidy were evaluated for 279 cases analyzed by NGS. Results: Excluding two cases (culture failure and maternal cell contamination), the results were consistent between G‐banding and NGS. For cases analyzed by NGS, the rate of chromosomal abnormality increased in a maternal age‐dependent manner. The frequency of each chromosomal aneuploidy detected by NGS was almost the same as that previously reported. Finally, NGS analysis was possible for difficult cases by G‐banding analysis, such as culture failure, maternal cell contamination, long‐term storage cases, and low cell number. Conclusions: Chromosome analysis using NGS not only obtains comparable results to conventional G‐banding, but also can analyze POC more accurately and efficiently.